Analisis strategi pengembangan digital banking pada bprs dalam meningkatkan loyalitas nasabah - ali, mochamad akbar fauzan (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the strategic development of digital banking in Islamic Rural Banks (BPRS) to enhance customer loyalty. The article employs a literature review approach by examining previous studies from 2015 to 2025 discussing digital innovation, service quality, and customer behavior in Islamic banking. The findings reveal that the implementation of digital banking in BPRS still faces several challenges, including limited technological infrastructure, low digital literacy among customers, and insufficient human resource readiness. Nevertheless, there are significant opportunities for development along with the growing demand for fast, convenient, and Sharia-compliant banking services. The recommended strategies for BPRS include enhancing digital capabilities, collaborating with Islamic fintech institutions, and applying technology-based customer relationship management. Through these strategies, BPRS is expected to improve service quality and foster long-term customer loyalty in the digital era.